2016
DOI: 10.1172/jci86826
|View full text |Cite
|
Sign up to set email alerts
|

A wandering path toward prevention for acute kidney injury

Abstract: A wandering path toward prevention for acute kidney injury Simon J. AtkinsonDepartment of Biology, Indiana University-Purdue University Indianapolis, Indianapolis, Indiana, USA. Acute kidney injury: challenges for therapy developmentAcute kidney injury (AKI) remains a serious complication in hospitalized patients, especially those that are critically ill (1, 2), and results in significant mortality and morbidity in this population. Those individuals that develop AKI and survive are at extremely high risk of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Acute kidney injury occurs in a variety of clinical scenarios with diverse manifestations ranging from a slight and sustained elevation in serum creatinine levels to anuric renal failure . AKI is commonly diagnosed in conjunction with a set of comorbid conditions including multiple organ sepsis, congestive heart failure or resulting major cardiothoracic surgery . AKI requiring dialysis is associated with a mortality rate ranging from 40% to 50%, and increasing to 60‐80% if combined with distant organ dysfunction states such as cardiac and respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute kidney injury occurs in a variety of clinical scenarios with diverse manifestations ranging from a slight and sustained elevation in serum creatinine levels to anuric renal failure . AKI is commonly diagnosed in conjunction with a set of comorbid conditions including multiple organ sepsis, congestive heart failure or resulting major cardiothoracic surgery . AKI requiring dialysis is associated with a mortality rate ranging from 40% to 50%, and increasing to 60‐80% if combined with distant organ dysfunction states such as cardiac and respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…Research on AKI is challenging as differentiation of underlying mechanisms in animal or in vitro models may differ to the complicated clinical presentation of patients in the intensive care units . Nevertheless, recent years have seen several exciting advancements in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, IAPs may involve in protective function of VNS and the inhibition of apoptosis when glutathione exerts antioxidant function. VNS has also been applied to IRI of the kidney [42], and the results of our proteomic analysis suggested that this regulatory approach is related to glutathione metabolism. We assumed that VNS could serve as a pretreatment before reperfusion, which might reduce inflammation and injury by adjusting the antioxidant capacity of the liver itself.…”
Section: Discussionmentioning
confidence: 94%
“…AKI is often caused by factors such as renal ischemia, severe infection and nephrotoxic drugs, of which the proportion of AKI induced by renal ischemia is as high as 50% 28 . Multiple mechanisms may explain the deterioration of AKI and its advancement towards chronic kidney disease (CKD), encompassing inflammation, angiotensin II, 29 renal nerves, 30 vagus nerves, 31 and neuro‐immunomodulatory mechanisms 31,32 . The kidney is innervated by an abundant assortment of efferent and afferent sympathetic nerves 33 .…”
Section: Discussionmentioning
confidence: 99%